Outcome of Cataract Surgery in Patients With Retinitis Pigmentosa - Nguyen, Xuan-Thanh-An; Thiadens, Alberta A H J; Fiocco, Marta; Tan, Weijen; McKibbin, Martin; Klaver, Caroline C W; Meester-Smoor, Magda A; Van Cauwenbergh, Caroline; Strubbe, Ine; Vergaro, Andrea; Pott, Jan-Willem R; Hoyng, Carel B; et al. (American journal of ophthalmology, 2023)
PURPOSE: To assess the visual outcome of cataract surgery in patients with retinitis pigmentosa (RP). DESIGN: Retrospective, noncomparative clinical study. METHODS: Preoperative, intraoperative, and postoperative data of patients with RP who were undergoing cataract surgery were collected from several expertise centers across Europe. RESULTS: In total, 295 eyes of 226 patients were included in the study. The mean age at surgery of the first eye was 56.1 ± 17.9 years. Following surgery, best-corrected visual acuity (BCVA) improved significantly from 1.03 to 0.81 logMAR (ie, 20/214 to 20/129 Snellen) in the first treated eye (-0.22 logMAR; 95% CI = -0.31 to -0.13; P < .001) and from 0.80 to 0.56 logMAR (ie, 20/126 to 20/73 Snellen) in the second treated eye (-0.24 logMAR; 95% CI = -0.32 to -0.15; P < .001). Marked BCVA improvements (postoperative change in BCVA of ≥0.3 logMAR) were observed in 87 of 226 patients (39%). Greater odds for marked visual improvements were observed in patients with moderate visual impairment or worse. The most common complications were zonular dialysis (n = 15; 5%) and (exacerbation of) cystoid macular edema (n = 14; 5%), respectively. Postoperative posterior capsular opacifications were present in 111 of 295 eyes (38%). CONCLUSION: Significant improvements in BCVA are observed in most patients with RP following cataract surgery. Baseline BCVA is a predictor of visual outcome. Preoperative evaluation should include the assessment of potential zonular insufficiency and the presence of CME, as they are relatively common and may increase the risk of complications.
Keywords: senioři; Retrospective Studies; Lens Implantation, Intraocular; Middle Aged; Capsule Opacification; Retinitis Pigmentosa; Adult; Phacoemulsification; retrospektivní studie; Humans; fakoemulzifikace; lidé středního věku; zkalení zadního pouzdra čočky; dospělí; retinopathia pigmentosa; Aged; implantace nitrooční čočky; katarakta; Cataract; lidé